2012
DOI: 10.1016/j.jcin.2012.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Vascular Healing in Response to Sirolimus- and Paclitaxel-Eluting Stents

Abstract: Early-generation drug-eluting stents show a similar degree of strut coverage and malapposition at 5 years of follow-up. Despite an overall low degree of uncovered and malapposed struts in event-free patients, some lesions show a clustering of these characteristics, indicating a heterogeneous healing response, which may be the source for very late adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…6,14 OCT studies have observed >5% of uncovered struts in >65% of patients with drug-eluting very-late ST. 6,16 Fiveyear OCT imaging of event-free patients treated with sirolimus-or paclitaxel-eluting stents showed that the percentage of patients with uncovered struts >5% was 10.7% with sirolimusand 7.2% with paclitaxel-eluting stents. 17 In the present study, including only STEMI patients, 32.3% and 6.5% of patients treated with EES and BMS had >5% of uncovered struts.…”
Section: Downloaded From the Re-examination Studymentioning
confidence: 46%
“…6,14 OCT studies have observed >5% of uncovered struts in >65% of patients with drug-eluting very-late ST. 6,16 Fiveyear OCT imaging of event-free patients treated with sirolimus-or paclitaxel-eluting stents showed that the percentage of patients with uncovered struts >5% was 10.7% with sirolimusand 7.2% with paclitaxel-eluting stents. 17 In the present study, including only STEMI patients, 32.3% and 6.5% of patients treated with EES and BMS had >5% of uncovered struts.…”
Section: Downloaded From the Re-examination Studymentioning
confidence: 46%
“…The multilevel logistic regression model as described above is estimated with a Bayesian approach based on uninformative priors 3,9 . The results obtained by the individual methods are presented in Table 1 and Figure 1.…”
Section: Bayesian Multilevel Modelmentioning
confidence: 99%
“…The conclusion of the multilevel models is correct but only as a statement regarding the majority of lesions; however, it does not capture the response of a few lesions with the highest level of malapposition. These lesions must be handled separately as done for example in Räber et al 9 . The GEE results are mainly driven by a few lesions.…”
Section: P-valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…2). 20 Early-generation sirolimus-and paclitaxeleluting stents were associated with delayed arterial healing -manifested as incomplete endothelialization of stent struts, vessel remodeling, and persistent fibrin and platelet deposition 20,21 -and with premature neoatherosclerosis. 22 Improved endothelial coverage has been reported after implantation of everolimus-and zotarolimus-eluting stents in studies in animals 23 and in clinical studies with intracoronary imaging.…”
Section: Arterial Healing After Stent Implantationmentioning
confidence: 99%